In situ growth of graphdiyne based heterostructure: Toward efficient overall water splitting. (May 2019) - Fang, Yan; Xue, Yurui; Hui, Lan; Yu, Huidi; Liu, Yuxin; Xing, Chengyu; Lu, Fushen; He, Feng; Liu, Huibiao; Li, Yuliang
Abstract: The controlled synthesis of graphdiyne-wrapped cobalt nitride nanosheets and their direct application as a bifunctional electrocatalyst towards electrical splitting water was reported for the first time. Because of its unique electronic and chemical structure, the electrocatalyst has high activity and stability in electrocatalysis process of 1.0 M KOH. The catalyst embedded by graphdiyne showed excellent catalytic performance of hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) with low overpotentials of 70 mV and 260 mV, respectively, at 10 mA cm −2, which was obviously superior to that of the commercial Pt/C and RuO2, respectively. As both the anode and cathode in a two-electrode alkaline electrolyzer, 10 mA cm −2 can be obtained at an ultralow cell voltage of 1.48 V which is much smaller than that of Pt/CRuO2 couple. Graphical abstract: Summary of the research:A new graphdiyne-wrapped cobalt nitride nanosheets array has been demonstrated to be an efficient HER/OER bifunctional electrocatalyst towards overall water splitting in alkaline conditions, exhibiting outstanding catalytic performances superior to that of commercial Pt/C for HER and RuO2 for OER, respectively.Image 1 Highlights: An in-situ growth method was applied to synthesize graphdiyne-wrapped cobalt nitride nanosheets. The graphdiyne triggered an energy favorable way for efficient water splitting. The resulting products exhibit outstanding catalytic performances superior to that of Pt/C for HER and RuO2 for OER.